Optimalisasi Self Care Management Diabetes pada Pasien Diabetes Mellitus di Puskesmas Parangloe Kabupaten Gowa - Wa Ode Sri Asnaniar; Nur Wahyuni Munir (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Management of Diabetes Mellitus (DM) aims to improve the quality of life for DM sufferers and reduce the risk of acute complications. Diabetes Self-Management Education (DSME) is a process that facilitates knowledge, skills, and abilities in self-care for DM patients based on evidence-based research. This activity aims to increase DM sufferers' knowledge and health status at Parangloe Health Center, Gowa Regency, South Sulawesi. The methods used are lectures, discussions, and demonstrations. The DSME administration was carried out in three sessions with 45 minutes and carried out diabetic foot gym training. Besides, the blood sugar level is checked at any time. The results achieved were an increase in knowledge of DM sufferers by 63.4% regarding definitions, classifications, signs and symptoms, risk factors, DM complications, diet, physical exercise, types and benefits of drugs given, foot care, and 96% being able to do foot exercises for diabetic. Also, there was an increase in the understanding and skills of cadres about DM self-care management. DM patients are also expected to check their blood glucose regularly and use the DM Self-Care Manual that has been provided.